1995
DOI: 10.1002/eji.1830250940
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐10 differentially regulates B7‐1 (CD80) and B7‐2 (CD86) expression on human peripheral blood dendritic cells

Abstract: Most of the immunosuppressive effects of interleukin-10 (IL-10) are related to functional inhibition of antigen-presenting cells (APC). Herein, we investigate the influence of recombinant (r)IL-10 on human dendritic cells (DC) purified from peripheral blood of healthy volunteers. First, we found that rIL-10 inhibited in a dose-dependent manner the proliferative responses as well as the production of IL-2 and interferon-gamma (IFN-gamma) in mixed lymphocyte reaction (MLR) between purified T cells and DC. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
127
1
5

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(145 citation statements)
references
References 31 publications
(11 reference statements)
10
127
1
5
Order By: Relevance
“…These results clearly indicate that mTORC1 positively regulates IL-10 expression in LP-DCs. Because IL-10 is known to suppress CD86 expression in DCs in vitro (16), it is likely that the increased expression of CD86 in LP-CD11c +…”
Section: Lp-cd11bmentioning
confidence: 99%
“…These results clearly indicate that mTORC1 positively regulates IL-10 expression in LP-DCs. Because IL-10 is known to suppress CD86 expression in DCs in vitro (16), it is likely that the increased expression of CD86 in LP-CD11c +…”
Section: Lp-cd11bmentioning
confidence: 99%
“…Therefore, DCs are believed to be largely plastic in function, and the expression of costimulatory markers and cytokines/molecules is likely to be more important for characterizing functional DC subsets. [78][79][80][81][82][83][84][85][86] Tolerogenic/regulatory DCs (DCregs), which may cause T-cell tolerance by different mechanisms, including T-cell depletion (apoptosis), T-cell hyporesponsiveness (anergy) and Treg induction, may be involved in the inhibition of allergic Th2 responses (Figure 1). Some CD8a 1 DCs express higher levels of Fas ligand (FasL) and are able to cause T-cell apoptosis.…”
Section: T-cell Responses and DC Functionmentioning
confidence: 99%
“…IL-10 is secreted by different tumors and may inhibit DC differentiation and function as well. 34,57 Wei and Jonakait 58 reported that IL-10 suppressed expression of CD40 molecules on cultured rat microglia. In addition, Tan et al 59 demonstrated that ligation of CD40 on cultured microglia cells by CD40L resulted in microglial activation, as measured by TNF-␣ production.…”
Section: Flt3l and Cd40l Administration In Mc38-bearing Mice Protectementioning
confidence: 99%